Interaction between biological and chemistry fungicides and tomato pollinators - De Melo e Silva-Neto, Carlos; Ribeiro, Anna Clara Chaves; Gómes, Flaviana Lima; Neves, Jordana Guimarães; Campos de Melo, Aniela Pilar; Calil, Francine Neves; Abadia dos Reis, Nascimento; Franceschinelli, Edivani Villaron (Universidad Pedagógica y Tecnológica de Colombia, 2019)
1 recurso en línea (páginas 425-435).